Harm reduction: buildind paths to caring - de Jesus Silva de Sousa, Francisco; Marcelle Martins Soares, Suzanne (Seven Editora, 2023)
T The expression harm reduction ( harm reduction ) has undergone a profound conceptual expansion and its historical construction justifies this fact since it is marked by a shift from the proposal of the control of infectious diseases to a set of policies and practices that, integrated with the actions of prevention, treatment, and social reintegration, aim to reduce individual and social damage related to the use of psychoactive substances (FONSÊNCA, 2012; TOTUGUI, 2009). Therefore, the purpose of this topic is to explore the emergence of Harm Reduction and its conceptual advances. It should be noted that the motivation for drawing this story is not to show the chronological course but to present the construction of meaning for the existence of harm reduction and the consolidation of a new paradigm of care within the scope of drugs. DOI: 10.56238/pacfdnsv1-097